Thyroid Cancer Bone Metastasis: Survival and Genomic Characteristics of a Large Tertiary Care Cohort. (August 2019) - Kondraciuk, Jessica D.; Rice, Samuel L.; Zhou, Xiaosun; Gharzeddine, Karem; Knezevic, Andrea; Spratt, Daniel E.; Sabra, Mona; Larson, Steven M.; Grewal, Ravinder K.; Osborne, Joseph R.
Purpose: Bone metastasis (BM) in differentiated thyroid cancer (DTC) is the second most common site of metastasis after lung. Bone metastases are associated with worse prognosis in DTC. In this study, we examined risk factors for overall survival in patients with BM and for the first time explore the pattern of genomic alterations in DTC BM. Patients and Methods: A Health Insurance Portability and Accountability Act (HIPAA) compliant, institutional review board–approved retrospective evaluation of the medical record was performed for all patients treated at a single institution for thyroid cancer over a 16-year period. Seventy-four patients met inclusion criteria. Multiple prognostic factors including age, sex, genes, radioactive iodine, and radiation or kinase inhibitor therapies were analyzed. Univariate and multivariate analyses were performed. Results: Treatment with external beam radiation was found to significantly increase survival ( P = 0.03). The 5-year survival rate was 59% and median survival was 92 months. Patients who developed bone metastasis earlier tend to live longer ( P = 0.06). The presence of TERT and BRAF mutations did not significantly worsen the prognosis ( P = 0.10). Conclusion: Patients with DTC can benefit from early treatment with external beam radiation therapy, especially those who develop bone metastasis within 3 years of primary TC diagnosis. Kinase inhibitor treatment tended to prolong survival but not in a statistically significant manner. Sex, age, and TERT or BRAF genetic mutations did not significantly affect the prognosis.